2018
DOI: 10.1016/j.artd.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve with a new primary total knee arthroplasty implant: a multicenter perspective with more than 2000 patients

Abstract: BackgroundThis study provides an example for evaluating learning curve when introducing a new knee system.MethodsThirty-five investigators across 22 sites prospectively implanted 843 subjects with currently available products (group A). Seventy-seven investigators across 48 sites prospectively implanted 2330 subjects with the ATTUNE Knee System; in which the first 10 subjects for each surgeon were the learning curve cases (group B, N = 611), and the later subjects were designated as group C (N = 1719). Surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…UKA has a longer learning curve compared with TKA techniques [31], for example 25 cases for Oxford UKA [44]. The learning curve found here was on par with those previously reported for navigated TKA systems of 10 cases [41] and slightly longer than robotic‐arm assisted systems for TKA of 7 cases [20]. Over 90% of knee surgeons perform under 12 UKA per year [25], and a short learning curve means that proficiency can be achieved sooner.…”
Section: Discussionsupporting
confidence: 71%
“…UKA has a longer learning curve compared with TKA techniques [31], for example 25 cases for Oxford UKA [44]. The learning curve found here was on par with those previously reported for navigated TKA systems of 10 cases [41] and slightly longer than robotic‐arm assisted systems for TKA of 7 cases [20]. Over 90% of knee surgeons perform under 12 UKA per year [25], and a short learning curve means that proficiency can be achieved sooner.…”
Section: Discussionsupporting
confidence: 71%
“…The first 10 New-TKA learning curve cases that each surgeon implanted were included in this study and have also been analyzed separately to explore the technically demanding skills associated with New-TKA adoption. 12 Both cohorts included all four TKA configurations (cruciate-retaining fixed bearing, cruciate-retaining rotating platform, posterior-stabilized fixed bearing, and posterior-stabilized rotating platform). Study investigators were trained on the New-TKA before enrollment and most attended cadaveric-based training.…”
Section: Methodsmentioning
confidence: 99%
“…Their study was, however, a retrospective study with a risk of selection bias, and all trainee surgeons had 2 years of surgical education prior to performing the surgery and were supervised throughout the operation by senior surgeons. Relatedly, a multicenter study examining the learning curve of a novel TKA introduction found no difference in intraoperative outcome and patient reported outcome measures (PROMs), and only a slight increase in operation time[ 15 ]. All surgeons in our study were very experienced at performing knee arthroplasty, thus limiting the learning curve.…”
Section: Discussionmentioning
confidence: 99%